2022
DOI: 10.3390/geotechnics2040050
|View full text |Cite
|
Sign up to set email alerts
|

Geological Exploration, Landslide Characterization and Susceptibility Mapping at the Boundary between Two Crystalline Bodies in Jajarkot, Nepal

Abstract: The geology of the Himalayas is intricated and intriguing. It features numerous tectonic bodies and structures too complex to interpret. Along with such mysteries it has too many common geohazards, such as landslides. In this study, a detailed geological investigation is carried out to overcome the discrepancies in structural interpretation, the nature of two crystalline bodies, and non-uniformity in geological mapping in the central Himalayan arc, in the Jajarkot district of Nepal. Along with the geological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The areas around the fault are more prone to landslides as the rocks in the proximity are disturbed and are generally weak. Faults also play a role in the movement of ground water, playing an important role in landslide occurrences 7 . During an earthquake, a fault may act as a barrier for the propagation of seismic waves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The areas around the fault are more prone to landslides as the rocks in the proximity are disturbed and are generally weak. Faults also play a role in the movement of ground water, playing an important role in landslide occurrences 7 . During an earthquake, a fault may act as a barrier for the propagation of seismic waves.…”
Section: Methodsmentioning
confidence: 99%
“…The stability of slopes is directly affected by anthropogenic factors such as road excavations 59 . Due to unplanned and nonengineered road construction, the mountainous regions of Nepal have experienced many landslides 7 . A significant number of landslide occurrences around roads after the 2015 Gorkha earthquake were reported by Mcadoo et al 60 .…”
Section: Methodsmentioning
confidence: 99%
“…Road distance is also one of the important causative factors considered in the occurrences of landslides. The field study revealed that haphazard road excavation without the consideration of geological and geotechnical features has caused shallow landslides (Budha et al 2016, Shahi et al 2022. The haphazard and unmanaged constructions of the roads built on the slopes cause the loss of support and bring changes in topography causing loss of support which ultimately leads to the increase of strain behind the slope and the development of cracks.…”
Section: Distance From Roadmentioning
confidence: 99%
“…The number of causative factors considered in this study is comparatively lower, but the success rates obtained are fine. Increasing the number of causative factors considered does not necessarily increase the model success rate significantly [69,70]. Currently, this paper presents four different models, namely the AHP, MLP, AHP-VW, and MLP-VW models, in which the single model AHP and MLP represent heuristic and statistical models, respectively.…”
Section: Comparison Of Modelsmentioning
confidence: 99%